Reliability of Greulich-Pyle Method in Comparing the Skeletal Age in Pukhtoons of District Peshawar (Medical Forum Monthly, 2024)
Objective: To compare the skeletal age in both genders in Pukhtoon population aged 11-16 years.Study design: Cross sectional/ non- interventional study.Place and Duration of Study: The study was conducted at Khyber Teaching Hospital and Forensic Department of Khyber Medical College. The duration of study was from December 2016 to May 2017.Materials and Methods: The study sample comprised of 600 healthy subjects in the age group of 11-16 years. Dates of birth of subjects were confirmed from their birth certificates and the chronological age was calculated properly. Hand-wrist radiographs were taken and bone age determined by Greulich-Pyle method.Results: A total of 600 subjects (male to female ratio 45.5:55.5) were evaluated for skeletal age by using Greulich-Pyle method of age determination. Chronological age was compared with skeletal age using the student “t” test in the study population comprising both genders. It was observed that females attained skeletal maturity earlier than the males.Conclusion: It was concluded that Pukhtoon children were more advanced in bone maturation than the Europeans. Furthermore, the females show earlier bone maturation than their male counterparts.This radiographic bone assessment can be correlated to assess the age in many medical and medicolegal cases.